Crown ether modified nanofiltration membrane, preparation method and application thereof

CN122974162APending Publication Date: 2026-10-27CHINA NAT OFFSHORE OIL CORP +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611318556.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]为了解决现有技术中冠醚修饰纳滤膜存在的冠醚结合不牢固、长期运行易流失、分离选择性不足以及水通量偏低等问题,本发明提供了一种制备过程简单、冠醚锚定稳定、离子选择性和水通量均显著提升的冠醚修饰纳滤膜制备方法,并实现其在废旧电池浸出液锂提取中的应用

Benefits of technology

(1)本发明首次在界面聚合过程中将4,10-二氮杂-12-冠-4醚与聚乙烯亚胺共同作为水相单体,通过与均苯三甲酰氯的一步界面聚合反应,将冠醚以酰胺键的形式共价锚定于聚酰胺分离层网络中,解决了传统冠醚改性纳滤膜中冠醚仅依靠物理吸附或氢键作用固定、长期运行易流失的突出问题。共价结合的膜结构在长期运行和酸性工况下表现出卓越的化学稳定性和可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974162A_ABST
    Figure CN122974162A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of membrane separation, and particularly discloses a crown ether modified nanofiltration membrane and a preparation method and application thereof, wherein a porous ultrafiltration membrane is used as a support layer, 4,10-diaza-12-crown-4 ether and polyethylene imine are used as water phase monomers, and trimesoyl chloride is used to form a polyamide separation layer on the surface of the ultrafiltration membrane through an interfacial polymerization reaction; wherein the 4,10-diaza-12-crown-4 ether reacts with the acyl chloride group of the trimesoyl chloride through its amino group to generate an amide bond and is anchored in the polyamide network in the form of a covalent bond. The cavity structure of the crown ether can provide a special transmission channel for Li+ and effectively intercept transition metal ions such as Ni 2+ , Co 2+ , Mn 2+ , so as to realize efficient and selective separation of lithium and transition metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membrane separation technology, and in particular to a crown ether modified nanofiltration membrane, its preparation method, and its application. Background Technology

[0002] Currently, lithium recovery from leachate of spent batteries mainly employs technologies such as solvent extraction, chemical precipitation, adsorption, and electrodialysis. Solvent extraction requires large amounts of organic solvents, posing environmental pollution risks and difficulties in extractant regeneration; chemical precipitation consumes large quantities of reagents, and the co-precipitation of lithium with transition metal ions is severe, leading to high lithium loss rates; adsorption is limited by the capacity and selectivity of the adsorbent, making it difficult to meet the needs of large-scale industrial applications; electrodialysis involves high equipment investment and high energy consumption. In contrast, nanofiltration technology, through the synergistic effect of pore size sieving and the Donnan repulsion effect, can selectively remove Li... + with Ni 2+ Co 2+ Mn 2+ Separation of isovalent transition metal ions has multiple advantages, including good selectivity, high separation efficiency, economic and environmental benefits, and simple operation. It is an important technical approach for the recovery of lithium from leachate of waste batteries.

[0003] Interfacial polymerization is currently the mainstream method for industrial preparation of nanofiltration membranes. Its principle involves cross-linking and polymerization at the interface of two immiscible solutions containing different reactive monomers to form a thin film separation layer. However, with increasingly complex treatment scenarios and higher performance requirements, traditional nanofiltration membranes face challenges such as poor separation efficiency and low water flux.

[0004] Crown ethers are a class of macrocyclic compounds with cyclic cavity structures, whose cavity size allows for the recognition and selective complexation of specific metal ions. Introducing crown ethers into nanofiltration membranes to construct channels with specific ion recognition and selective transport, thereby significantly improving membrane separation performance, has become an important technological direction for nanofiltration membrane modification in recent years.

[0005] In existing technologies, the introduction of crown ethers into nanofiltration membranes mainly includes physical blending and surface coating modification. For example, Chinese patent application CN102604138A discloses a chitosan-based membrane. However, the crown ethers introduced by this type of physical blending are only maintained by weak interactions such as hydrogen bonds or van der Waals forces with the polymer matrix. During long-term operation, crown ether molecules are easily lost from the membrane, leading to a gradual decline in separation performance. Under acidic conditions such as leachate from spent batteries, hydrogen-bonded crown ethers are more prone to dissociation, causing loss of membrane selectivity. Furthermore, simple physical blending can easily lead to uneven dispersion of crown ethers in the membrane, forming non-selective interface defects and affecting the membrane's retention performance.

[0006] Researchers have attempted to introduce crown ethers into nanofiltration membranes using a secondary interfacial polymerization method. For example, Chinese invention patent application CN120827815A discloses a crown ether-functionalized negatively charged nanofiltration membrane based on secondary interfacial polymerization. This method involves introducing amine-containing crown ethers onto the membrane surface after the initial polyamide membrane is formed via secondary interfacial polymerization. However, this secondary interfacial polymerization method is cumbersome, and the crown ethers are mainly located on the membrane surface, making them easily washed away by water flow, resulting in insufficient long-term operational stability. Furthermore, if the crown ethers and polyamines are linked solely by hydrogen bonds, the bonding strength is relatively weak, and the membrane structure is prone to failure under long-term operation or acidic conditions. In actual lithium extraction from waste battery leachates, the leachate is typically strongly acidic (pH approximately 2-3), placing higher demands on the chemical stability of the membrane.

[0007] Therefore, there is an urgent need to develop a crown ether-modified nanofiltration membrane with a simple preparation process, strong crown ether anchoring, high separation selectivity, and good operational stability to meet the practical needs of efficient separation of lithium and transition metal ions in waste battery leachate. Summary of the Invention

[0008] To address the problems of weak crown ether binding, easy loss during long-term operation, insufficient separation selectivity, and low water flux in existing crown ether-modified nanofiltration membranes, this invention provides a method for preparing crown ether-modified nanofiltration membranes that is simple to prepare, has stable crown ether anchoring, and significantly improves ion selectivity and water flux. This method is then applied to lithium extraction from waste battery leachate.

[0009] To achieve the above objectives, the present invention is implemented according to the following technical solution: The first technical solution provided by this invention is a method for preparing a crown ether-modified nanofiltration membrane, comprising the following steps: S1. Dissolve 4,10-diaza-12-crown-4 ether, polyethyleneimine, sodium dodecyl sulfate, and sodium carbonate in deionized water and stir until homogeneous to obtain an aqueous solution. Dissolve pyromellitic methyl chloride in n-hexane and stir until homogeneous to obtain an oil solution. S2. Immerse the porous ultrafiltration membrane base membrane in an ethanol solution, remove it, rinse it, and then soak it in deionized water. S3. Pour the aqueous solution onto the surface of the base film, soak it, remove excess liquid, and dry until there are no obvious droplets on the film surface. S4. Coat the oil phase solution onto the membrane surface and carry out the interfacial polymerization reaction. After the reaction is complete, remove the excess solution and rinse the surface with n-hexane. S5. Place the membrane in an oven for heating treatment to obtain a crown ether modified nanofiltration membrane.

[0010] Further, in step S1, the mass concentration of 4,10-diaza-12-crown-4 ether in the aqueous phase solution is 0~0.1%, the mass concentration of polyethyleneimine is 0.1~0.5%, the mass concentration of sodium dodecyl sulfate is 0.1%, and the mass concentration of sodium carbonate is 0.1%; the mass concentration of pyromellitic acid chloride in the oil phase solution is 0.05~0.15%.

[0011] Preferably, the mass concentration of 4,10-diaza-12-crown-4 ether in the aqueous solution in step S1 is 0.06%.

[0012] Preferably, in step S2, the mass concentration of the ethanol solution is 30%, the porous ultrafiltration membrane base membrane is soaked in the ethanol solution for 30 minutes, and soaked in deionized water for 6 hours.

[0013] Preferably, the time for coating the oil phase solution onto the membrane surface in step S4 is 1 to 5 minutes.

[0014] Preferably, in step S5, the oven temperature is set to 50~90℃ and the heat treatment time is 0~20min.

[0015] The second technical solution provided by this invention is a crown ether modified nanofiltration membrane prepared by the above method.

[0016] The third technical solution provided by this invention is the application of the crown ether modified nanofiltration membrane in the separation of lithium and transition metal ions in the leachate of waste batteries.

[0017] The technical mechanism of this invention lies in the fact that 4,10-diaza-12-crown-4 ether has a ring-shaped cavity of suitable size, the diameter of which is similar to that of Li + The ion diameters are relatively well-matched, while Ni, with its larger hydrated ion radius, is more suitable. 2+ Co 2+ Mn 2+ Transition metal ions exhibit significant steric hindrance. When ions pass through the crown ether cavity, bound water in their hydration shell needs to be removed. (Li) + The dehydration energy is much lower than that of Ni. 2+ Co 2+ and Mn 2+ Therefore, in terms of energy, Li + It is easier to pass through the crown ether cavity. At the same time, 4,10-diaza-12-crown-4 ether is covalently anchored in the polyamide separation layer network through amide bonds, which effectively prevents the loss of crown ether molecules during long-term operation and ensures the long-term stability of membrane separation performance.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention is the first to use 4,10-diaza-12-crown-4 ether and polyethyleneimine as aqueous monomers in the interfacial polymerization process. Through a one-step interfacial polymerization reaction with trimesoyl chloride, the crown ether is covalently anchored in the polyamide separation layer network in the form of amide bonds. This solves the prominent problem in traditional crown ether-modified nanofiltration membranes where the crown ether is fixed only by physical adsorption or hydrogen bonding and is prone to loss during long-term operation. The covalently bonded membrane structure exhibits excellent chemical stability and reliability under long-term operation and acidic conditions.

[0019] (2) This invention utilizes the size effect of the cyclic cavity of 4,10-diaza-12-crown-4 ether and the difference in ion dehydration energy to construct Li + A dedicated transmission channel enables the processing of Li in complex systems of waste battery leachate. + Highly efficient and selective transport of Ni. Experiments show that under optimized conditions, the separation factors for nickel and lithium reach 37.66, for cobalt and lithium 40.67, and for manganese and lithium 31.35, representing a factor-fold improvement compared to the unmodified membrane (corresponding separation factors of 15.17, 14.42, and 13.43, respectively). Simultaneously, the membrane exhibits high efficiency and selectivity in transporting Ni. 2+ Co 2+ Mn 2+ The retention rate has remained above 91%.

[0020] (3) The water flux of the nanofiltration membrane prepared by the method of the present invention is significantly improved, reaching 10.59 L·m under optimized conditions. -2 ·h -1 ·bar -1 The value is approximately 5.29 L·m⁻¹ of the unmodified film. -2 ·h -1 ·bar -1 The water flux is twice that of the crown ether, and the water flux increases with the amount of crown ether added, indicating that the cavity structure of the crown ether effectively increases the permeation channels of water molecules.

[0021] (4) The preparation method provided by the present invention adopts a one-step interfacial polymerization process, which is simple, mild and low cost. It does not require pre-modification of crown ether or secondary interfacial polymerization, and is easy to realize industrial scale-up production. It has broad application prospects in the field of lithium extraction from waste battery leachate and lithium secondary resource recycling. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the nanofiltration membrane preparation method of the present invention.

[0023] Figure 2 This is a schematic diagram of the nanofiltration membrane preparation mechanism of the present invention.

[0024] Figure 3The following are surface and cross-sectional electron microscopy (SEM) images of the porous ultrafiltration membrane base used in this invention: (a) is a surface SEM image; (b) is a cross-sectional SEM image.

[0025] Figure 4 The surface and cross-sectional SEM images of the nanofiltration membrane prepared in Example 3 of the present invention are shown below: (a) is the surface SEM image; (b) is the cross-sectional SEM image.

[0026] Figure 5 The following are surface and cross-sectional electron microscopy (SEM) images of the nanofiltration membrane prepared in Comparative Example 1 of this invention: (a) is a surface SEM image; (b) is a cross-sectional SEM image. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0028] Example 1: Figure 1 This is a schematic flowchart of the nanofiltration membrane preparation method of the present invention, clearly showing five main steps: base membrane pretreatment, aqueous phase casting, oil phase coating, interfacial polymerization reaction, and heat treatment. The specific steps are as follows: (1) Dissolve 0.02% 4,10-diaza-12-crown-4 ether, 0.3% polyethyleneimine, 0.1% sodium dodecyl sulfate, and 0.1% sodium carbonate in deionized water and stir until homogeneous to obtain an aqueous solution. Dissolve trimesoyl chloride in n-hexane and stir until homogeneous to obtain a 0.125% trimesoyl chloride oil solution. (2) The porous ultrafiltration membrane base membrane (SEM images of the surface and cross-section of the porous ultrafiltration membrane base membrane are shown in Figure 1) Figure 3 As shown, Figure 3 The base film (which has a smooth surface and a porous structure) was immersed in a 30% ethanol solution for 30 minutes, then removed, rinsed 3 times, and then soaked in deionized water for 6 hours. (3) Pour the aqueous phase onto the surface of the base membrane, soak for 5 minutes, then pour off the excess liquid and let it dry at room temperature until there are no obvious droplets on the membrane surface. (4) Coat the oil phase solution onto the membrane surface, perform interfacial polymerization, and after wetting for 2 minutes, pour off the excess solution and rinse the surface thoroughly with n-hexane. (5) Finally, the membrane is placed in an oven and heat-treated at 70°C for 10 minutes. Then it is taken out and stored in deionized water to obtain a nanofiltration membrane.

[0029] Figure 2This is a schematic diagram of the nanofiltration membrane preparation mechanism of the present invention, showing the process by which aqueous monomers (4,10-diaza-12-crown-4 ether and polyethyleneimine) and oil monomers (pyromellitic trichomeoyl chloride) undergo a polymerization reaction at the interface to form a polyamide separation layer with covalently anchored crown ether.

[0030] Example 2: The difference between this example and Example 1 is that the mass concentration of 4,10-diaza-12-crown-4 ether in the aqueous solution is adjusted to 0.04%, while the rest of the preparation process is the same as in Example 1, and a nanofiltration membrane is obtained.

[0031] Example 3: The difference between this example and Example 1 is that the mass concentration of 4,10-diaza-12-crown-4 ether in the aqueous solution is adjusted to 0.06%, while the rest of the preparation process is the same as in Example 1, and a nanofiltration membrane is obtained. Figure 4 The images show surface and cross-sectional SEM images of the nanofiltration membrane prepared according to an embodiment of the present invention. It can be seen that a uniform and dense polyamide separation layer is formed on the membrane surface after interfacial polymerization.

[0032] Example 4: The difference between this example and Example 1 is that the mass concentration of 4,10-diaza-12-crown-4 ether in the aqueous solution is adjusted to 0.08%, while the rest of the preparation process is the same as in Example 1, and a nanofiltration membrane is obtained.

[0033] Example 5: The difference between this example and Example 1 is that the mass concentration of 4,10-diaza-12-crown-4 ether in the aqueous solution is adjusted to 0.1%, while the rest of the preparation process is the same as in Example 1, and a nanofiltration membrane is obtained.

[0034] Comparative Example 1 The difference between this comparative example and Example 1 is that the mass concentration of 4,10-diaza-12-crown-4 ether in the aqueous solution was adjusted to 0. All other preparation processes were the same as in Example 1. Nanofiltration membranes were obtained, and SEM images of the surface and cross-section of the nanofiltration membranes are shown below. Figure 5 As shown. With Figure 4 As can be seen from the comparison, the surface morphology and cross-sectional structure of the membrane changed after the introduction of crown ether.

[0035] The nanofiltration membranes prepared in Examples 1-5 and Comparative Example 1 were subjected to performance tests using simulated spent lithium battery leachate. The Li in the simulated leachate... + Ni 2+ Co 2+ Mn 2+ The ion concentrations were 126, 438 mg / L, 244 mg / L, and 500 mg / L, respectively, the pH value was 2.5, and the anion was Cl. -The tests were conducted in a cross-flow filtration device at a temperature of 25°C and a pressure of 5 bar. The rejection rates of each metal ion and the water flux of each membrane were measured, and the separation factor was calculated. The rejection rates of each metal ion and the water flux data are shown in Tables 1 and 2, respectively, and the separation factor is shown in Table 3.

[0036] Table 1

[0037] Table 2

[0038] Table 3

[0039] Note: The separation factor is calculated as SF(A / Li) = [(100-R_Li) / (100-R_A)], where R is the rejection rate.

[0040] As can be seen from Tables 1, 2, and 3, the introduction of 4,10-diaza-12-crown-4 ether during interfacial polymerization significantly affects the separation performance of the nanofiltration membrane. Combining the data from Tables 1 and 2, the modified membranes prepared in Examples 1-5 maintain their resistance to Ni... 2+ Co 2+ Mn 2+ While maintaining high rejection rates for transition metal ions (all above 91%), its water flux was lower than that of Comparative Example 1 (5.29 L·m⁻¹). -2 ·h -1 ·bar -1 All showed significant improvements. Specifically, the water flux in Example 3 reached 10.59 L·m³. -2 ·h -1 ·bar -1 The water flux was approximately twice that of Comparative Example 1. This is attributed to the inherent cyclic cavity structure of 4,10-diaza-12-crown-4 ether, which increases the permeation channels for water molecules. Looking at the trend of water flux change, as the crown ether addition increased from 0.02% to 0.1%, the water flux gradually increased from 7.72 L·m⁻¹ to 11.46 L·m⁻¹. -2 ·h -1 ·bar -1 This indicates that more crown ether molecules provide more permeation pathways for water molecules.

[0041] Regarding lithium-ion transport, Example 3 focuses on Li + The retention rate was only 28.83%, significantly lower than the 39.16% of the control group 1, indicating that the crown ether cavity effectively promoted the Li +Transmembrane transport. As shown in Table 3, the separation factors of nickel-lithium, cobalt-lithium, and manganese-lithium in Example 3 are as high as 37.66, 40.67, and 31.35, respectively, which are several times higher than those in Comparative Example 1 (corresponding to 15.17, 14.42, and 13.43, respectively).

[0042] It is noteworthy that, with further increases in crown ether content (Examples 4 and 5), although the water flux continued to rise, the separation factor began to decrease, and Ni... 2+ Co 2+ Mn 2+ The retention rate also decreased. This may be because the introduction of excessive crown ether molecules interfered with the crosslinking density of the polyamide layer to some extent, leading to enhanced non-selective penetration of transition metal ions. Therefore, a mass concentration of 0.06% for 4,10-diaza-12-crown-4 ether (Example 3) is the optimal ratio of the present invention, which can achieve the desired effect in Li + The optimal balance is achieved among selectivity, transition metal ion rejection rate, and water flux.

[0043] The improved membrane performance stems from the covalent bonding of 4,10-diaza-12-crown-4 ether to the polyamide separation layer. Its unique cavity structure allows for the formation of Li... + Provides a dedicated transport channel. Because different ions need to remove bound water when passing through the crown ether cavity, and Li... + The hydration energy required to remove bound water is much lower than that required for Ni. 2+ Co 2+ Isovalent transition metal ions, thus realizing Li + It enables highly efficient and selective transmembrane transport. Simultaneously, the stable amide bond structure formed by covalent bonds ensures the structural stability of the membrane under complex waste battery leachate processing conditions, effectively preventing the loss of functional units and guaranteeing the long-term stability of the separation process.

[0044] The technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made in accordance with the technical solutions of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a crown ether-modified nanofiltration membrane, characterized in that, Includes the following steps: S1. Dissolve 4,10-diaza-12-crown-4 ether, polyethyleneimine, sodium dodecyl sulfate, and sodium carbonate in deionized water and stir until homogeneous to obtain an aqueous solution. Dissolve pyromellitic methyl chloride in n-hexane and stir until homogeneous to obtain an oil solution. S2. Immerse the porous ultrafiltration membrane base membrane in an ethanol solution, remove it, rinse it, and then soak it in deionized water. S3. Pour the aqueous solution onto the surface of the base film, soak it, remove excess liquid, and dry until there are no obvious droplets on the film surface. S4. Coat the oil phase solution onto the membrane surface and carry out the interfacial polymerization reaction. After the reaction is complete, remove the excess solution and rinse the surface with n-hexane. S5. Place the membrane in an oven for heating treatment to obtain a crown ether modified nanofiltration membrane.

2. The method for preparing crown ether-modified nanofiltration membrane according to claim 1, characterized in that: In step S1, the aqueous solution contains 0-0.1% 4,10-diaza-12-crown-4 ether, 0.1-0.5% polyethyleneimine, 0.1% sodium dodecyl sulfate, and 0.1% sodium carbonate; the oil solution contains 0.05-0.15% pyromellitic acid chloride.

3. The method for preparing crown ether-modified nanofiltration membrane according to claim 2, characterized in that: The mass concentration of 4,10-diaza-12-crown-4 ether in the aqueous solution in step S1 is 0.06%.

4. The method for preparing crown ether-modified nanofiltration membrane according to claim 1, characterized in that: In step S2, the mass concentration of the ethanol solution is 30%, the porous ultrafiltration membrane base membrane is soaked in the ethanol solution for 30 minutes, and soaked in deionized water for 6 hours.

5. The method for preparing crown ether-modified nanofiltration membrane according to claim 1, characterized in that: In step S4, the oil phase solution is coated onto the membrane surface for 1 to 5 minutes.

6. The method for preparing crown ether-modified nanofiltration membrane according to claim 1, characterized in that: In step S5, the oven temperature is set to 50~90℃ and the heat treatment time is 0~20min.

7. A crown ether-modified nanofiltration membrane prepared by the method according to any one of claims 1-6.

8. The application of a crown ether modified nanofiltration membrane as described in claim 7 in the separation of lithium and transition metal ions in leachate from waste batteries.

Citation Information

Patent Citations

  • Method for preparing chitosan substrate film by self-deposition of micron gel

    CN102604138A

  • Crown ether functionalized negatively-charged nanofiltration membrane based on secondary interfacial polymerization as well as preparation method and application of crown ether functionalized negatively-charged nanofiltration membrane

    CN120827815A